Ensuring productivity advantages through Cluster Frontline Demonstrations (CFLD)-pulses: Nationwide experiences - SINGH, ATAR; SINGH, A K; DUBEY, S K; CHAHAL, V P; SINGH, RANDHIR; MISHRA, ANUPAM; SINGH, RAJBIR; DEKA, B C; SINGH, S K; SINGH, S S; SINGH, LAKHAN; TRIPATHI, A K; et al. (The Indian Journal of Agricultural Sciences, 2023)
The present study is the analysis of large scale data (31949 ha area and 79873 farmers) generated through the CFLD on pulses across the major pulses growing states under the ICAR-ATARIs of Kanpur (Uttar Pradesh), Jodhpur (Rajasthan), Pune (Maharashtra), Patna (Bihar), Jabalpur (Madhya Pradesh), Kolkata (West Bengal), Guwahati (Assam), Shillong (Meghalaya), Hyderabad (Andhra Pradesh), Bengaluru (Karnataka) and Patna (Bihar). The pulse crops included in this analysis were from all three growing seasons: kharif (pigeonpea-5556 ha, blackgram-6067 ha, and greengram-2689 ha), rabi (chickpea-8376 ha, lentil-3747 ha and field pea-1890 ha), and summer (greengram-3624 ha). The average performance data of CFLD were obtained for the above states for all the crops representing all three growing seasons during the cropping seasons of 2016–17 and 2017–18. Thus, CFLD data were analyzed fromacross minimum of 21 states (greengram) and maximum of 24 states (blackgram). The major variables analyzed were average yield obtained from the check plots and demonstrations plots. These yields were computed for yield advantages and also compared with the reported district level, state level, national level yields and the potential yields of the respective crops in the given states (data procured from secondary sources for the year 2017–18). Accordingly, the yield advantages (absolute as well as per cent) at various level were analyzed and their degree of variation was computed for all the crops across the seasons. The paper brings out the results of above analyses in objective manner.